2019
DOI: 10.3390/molecules24142631
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Derivatives as a Potential Agent against Antimicrobial Resistance (AMR) Pathogens

Abstract: The evolution of antimicrobial resistance (AMR) in pathogens has prompted extensive research to find alternative therapeutics. Plants rich with natural secondary metabolites are one of the go-to reservoirs for discovery of potential resources to alleviate this problem. Terpenes and their derivatives comprising of hydrocarbons, are usually found in essential oils (EOs). They have been reported to have potent antimicrobial activity, exhibiting bacteriostatic and bactericidal effects against tested pathogens. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
178
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(188 citation statements)
references
References 106 publications
2
178
0
8
Order By: Relevance
“…Each of these constituents has a different number of isoprene units, forming an aromatic ring structure. Depending on the characteristic of these isoprenes, the EO constituent can be either aromatic or non-aromatic compounds (Trombetta et al 2005;Gallucci et al 2009;Morsy 2017;Mahizan et al 2019). Terpenoids are derived from terpenes with the modification through the addition or removal of functional groups (Mahizan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these constituents has a different number of isoprene units, forming an aromatic ring structure. Depending on the characteristic of these isoprenes, the EO constituent can be either aromatic or non-aromatic compounds (Trombetta et al 2005;Gallucci et al 2009;Morsy 2017;Mahizan et al 2019). Terpenoids are derived from terpenes with the modification through the addition or removal of functional groups (Mahizan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the characteristic of these isoprenes, the EO constituent can be either aromatic or non-aromatic compounds (Trombetta et al 2005;Gallucci et al 2009;Morsy 2017;Mahizan et al 2019). Terpenoids are derived from terpenes with the modification through the addition or removal of functional groups (Mahizan et al 2019). Terpenes can have different chemical functional groups including alcohol, aldehyde, phenol, ketone, ether, and hydrocarbon groups (Guimarães et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these functional groups increases the structure electronegativity, which may interfere with biological processes involving electron transfer and react with vital nitrogen components, such as proteins and nucleic acids, and consequently inhibit bacterial growth [34]. Moreover, monoterpenes consisting of aldehydes possess antimicrobial activity, which can be explained through their carbon double bond arrangements creating high electronegativity (reviewed by Mahizan et al [35]). The presence of the acetate moiety in terpenoid chemical structures is also crucial to increase toxicity, which was confirmed when the activity of α-terpineol against V. fischeri was compared to (±)-α-terpinyl acetate (Figure 3).…”
Section: Toxicity Of Terpenoidsmentioning
confidence: 99%
“…Regardless of continuous and progressive achievements in the area of medical field, there are impending threats which cannot be overlooked. One such threat would be the rise in antimicrobial resistance among pathogens due to over-prescription and also the development of resistance among cancer-curing drugs through DNA mutation by the cancerous cells [4][5][6][7]. Figure 1, below, shows the percentage of deaths caused in the world due to communicable and non-communicable diseases in 2017 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to look into alternative solutions, such as natural products, for example, plant extracts, to overcome impending threats in the medical field [11,12]. It has been widely reported that plant extracts such as essential oils contain various bioactive compounds which are responsible for bioactivities, such as antimicrobial, anticancer, and anti-inflammatory agents [6,[12][13][14][15]. As nature is rich with different plants, researchers have focused their attention towards plant extracts as an alternative to synthetic drugs to be applied in the clinical setting [16].…”
Section: Introductionmentioning
confidence: 99%